ANALISIS TINDAK TUTUR ANTARA PENJUAL DAN PEMBELI DI PASAR SUMBERAYU MUNCAR BANYUWANGI ( KAJIAN PRAGMATIK ) TAHUN 2020 - M. Hasbullah Ridwan; Muhammad Abu Riza (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2021)
Speech acts are actions that are displayed through speech. This means that something like that contains an assumption that the utterances we speak are not really empty speeches without any action content in them, or empty of the current context. Speech acts are divided into three types, namely speech acts of locus, illocution and perlocution. The problems discussed in this research are 1) What are the forms of speech acts between the seller and the buyer at Sumberayu Market, Muncar Banyuwangi? 2) It is included in the category of speech acts whether the utterances uttered by sellers and buyers at Sumberayu Muncar Banyuwangi Market. This study aims to determine the forms of speech acts between sellers and buyers at Sumberayu Muncar Banyuwangi Market, and to find out the meaning contained in the the form of speech acts and including the category of speech acts whether the utterances spoken by the seller and the buyer at Sumberayu Market Muncar Banyuwangi. Researchers here use a qualitative approach. A qualitative approach is an approach based on a natural or naturalist background. Research data collection techniques using observation techniques and note-taking techniques, data analysis techniques flow analysis methods which include data reduction, data presentation and drawing conclusions / verification. The results of the study were speech acts which consisted of 19 forms of conversation consisting of 86 locusive speech acts, 20 illocutionary speech acts, and 14 perlocutionary speech acts which were spoken between sellers and buyers consisting of vegetable sellers, fruit-fruit sellers, ampok rice sellers, traditional hawker sellers, soybean sellers and others.